Merry Christmas, Splat - Scotton, Rob (New York : Harper, 2009)
Splat the cat is worried that he has not been good enough to deserve a visit and a present from Santa Claus.
Ages 3-7.
Keywords: Cats -- Fiction; Christmas -- Fiction; Behavior -- Fiction